A pedicled split extended vertical deep inferior epigastric (s‐vDIEP) flap and an adipo‐dermal thigh local flap for the reconstruction of the medial thigh compartment after sarcoma resection: A case report. Issue 1 (17th December 2018) - Scaglioni, Mario F.; Giunta, Gabriele; Barth, Andrè A.; Giovanoli, Pietro
Abstract : Large upper medial thigh defects in prior irradiated tissue require challenging reconstructions. Several techniques have been reported to reconstruct this region and according to the literature, pedicled perforator flaps are the first reconstructive option. The anterolateral thigh flap is considered the gold standard, while surprisingly the pedicle deep inferior epigastric (DIEP) flap in vertical fashion has not been frequently employed, if compared with its muscular counterpart, the pedicle vertical rectus abdomins flap (vRAM). We report a case of a multilayered flaps reconstruction of the left medial thigh after an excision of a sarcoma involving the whole adductors compartment. A 75‐year‐old male patient underwent a free margins resection of the sarcoma. After the resection, a soft tissue defect of 24 cm × 14 cm × 14 cm spreading from the groin to the medial tuberosity of the tibia, was left. We performed a reconstructive technique based on a pedicled split extended vertical deep inferior epigastric (s‐vDIEP) flap and an adipo‐dermal thigh local flap in order to fill and cover the thigh defect. The s‐vDIEP had 2 islands: a cranial de‐epithelialized island to fill the dead space and a caudal for the skin closure. The postoperative follow‐up was complicated by seroma formation and it was managed by sclerotherapy and at the 6 months follow‐up the patient showed good cosmetic and functional outcomes with no sign of tumor relapse. Our result suggests that the proposed multilayered reconstruction may be employed for the restoration of large and deep upper medial thigh defects.